A Multicenter, Randomized, Trial Comparing Urapidil and Nitroglycerin in Multifactor Heart Failure in the Elderly. (August 2015) - Yang, Wei; Zhou, Yu-Jie; Fu, Yan; Qin, Jian; Qin, Shu; Chen, Xiao-Min; Guo, Jin-Cheng; Hua, Qi
Abstract: Background: Multifactor heart failure is a common life-threatening event in elderly patients and often complicated by concomitant hypertension and diabetes mellitus (DM). The aim of this study was to evaluate whether α1-blocker, urapidil, provides additional therapeutic benefits compared to nitroglycerin (NG) in treatment of multifactor heart failure complicated by hypertension and DM in elderly patients. Methods: Seventy-two elderly consecutive patients were randomized into 2 groups that received treatment with urapidil or NG. All patients were monitored for blood pressure (BP) and heart rate and received tests for metabolic activity and cardiovascular function. Results: Patients receiving urapidil had significantly lower systolic BP than their counterparts in NG group ( P < 0.05). Moreover, patients in urapidil group showed lower N-terminal pro-B-type natriuretic peptide levels but higher ejection fraction ( t = 2.206, P < 0.05), cardiac index ( t = 3.13, P < 0.05) and left end-diastolic volume ( t = −3.104, P < 0.05) compared to NG group. Although both urapidil and NG decreased fasting plasma glucose (FPG) levels, there was no significant difference of FPG levels between these 2 groups. Conclusions: Urapidil demonstrated better efficacy than NG on lowering and stabilizing systolic BP, attenuating cardiac afterload and improving cardiac function. Both NG and urapidil significantly reduced FPG levels in multifactor heart failure patients with DM. Urapidil is a therapeutic option for the multifactor heart failure patients complicated with hypertension and DM.